2019
DOI: 10.22158/jecs.v4n1p19
|View full text |Cite
|
Sign up to set email alerts
|

Measuring Disciplinary Perceptions of Engineering from a Cultural Lens: A Validation of an Instrument in a Research Technical University

Abstract: Engineering culture is a complex phenomenon that needs to be understood to promote the value of professional skills and not only the technical skills that have been traditionally valued in engineering. This study investigates ways to identify patterns of cultural traits in undergraduate engineering students, by using and validating an instrument originally developed to measure national culture. This study was conducted in three phases: in Phase 1, we validated an instrument to measure engineering culture based… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(15 citation statements)
references
References 15 publications
0
10
0
Order By: Relevance
“…To assess the quality of the research, the study stands on previous studies conducted by one of the authors [4], [6], [35]. Content validity was discussed and determined by the researchers in consensus [36].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…To assess the quality of the research, the study stands on previous studies conducted by one of the authors [4], [6], [35]. Content validity was discussed and determined by the researchers in consensus [36].…”
Section: Methodsmentioning
confidence: 99%
“…Content validity was discussed and determined by the researchers in consensus [36]. Construct validity is addressed by using a survey that has been proven to be an effective tool to assess the cultural dimensions of a group [24], [29], [30], [37], [38] and the authors even demonstrated its validity in academic settings [4].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to better understand the differences between personal cultural orientation in engineering students from the U.S. and Ecuador, data were collected quantitatively using a survey adapted by Sharma [4] to measure Hofstede's cultural dimensions within engineering students. This survey was not only validated by Sharma [4] but also the authors validated it for its use in academic disciplines [15].…”
Section: Methodsmentioning
confidence: 99%
“…Masculine cultures thus experience a greater gap between men's and women's roles [9], [10], [12] Despite Hofstede's theory receiving some criticism (see [14] for full details), we consider there is value in testing Hofstede's theory of dimensions of national culture in academic settings. Hofstede's model uses dimensions of culture that have been validated in a variety of contexts and scenarios [14], [15], and we have been using his theory to explore different engineering disciplines [6]- [8], [8], [14].…”
Section: Theoretical Frameworkmentioning
confidence: 99%